PENGARUH MODEL PEMBELAJARAN MATEMATIKA REALISTIK TERHADAP PEMAHAMAN KONSEP SISWA KELAS IV MI HIDAYATUL MUBTADI’IN TASIKMADU MALANG - Nurul Husniyah; Ika Ratih Sulistiani; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstractThis study aims to: (1) describe the results of conceptual understanding in the fourth grade of MI Hidayatul Mubtadiin in Tasikmadu Malang and (2) to find out whether there is any influence on the realistic learning model on understanding the concept of fourth grade students of Hidayatul Mubtadi'in Tasikmadu Malang. This research was conducted in May at MI Hidayatul Mubtadiin in Malang with a total of 26 students as the experimental class and MI Raudlatul Mubtadiin Wonokasian Turen Malang with a total of 32 students as a control class, in the school year 2018-2019. This type of research is a quasi-experimental (quasi-experimental) design with pre-test and post-test. Data analysis techniques carried out include the instrument test, validity test, reliability test, prerequisite test: prerequisite test, homogeneity test, hypothesis test and t-test test. From the results of this study it is known that the use of this learning model gets a significant value on students' understanding of concepts with the acquisition of a significance value of 0,000, which is the basis of decision making if the value of sig. (2-tailed) 0,000 <0,05, there is a significant difference in understanding of concepts.Keyword : Models of teaching, Mathematic, Realistic